Isolation and molecular identification of Colletotrichum gleosporiodes from infected peanut seeds - Rajeendran, Allegendran; Nulit, Rosimah; Yong, Christina Seok Yien; Ibrahim, Mohd. Hafiz; Kalhori, Nahid (SCIENCEDOMAIN international, 2017)
Peanut (Arachis hypogaea(L) cv. Margenta) seeds are currently, significantly considered as an important source of protein and vegetable oil. Anthracnose caused by Colletotrichum gloeosporioidesis a fungal disease from seed that reduces seedling emergence and seed germination. The pathogenic fungi that isolated from peanut were identified using ITS 1and ITS 4 primer with polymerase chain reaction and NCBI database using BlastN algorithm. From NCBI using blastN analysed was 95% identify with other Colletotrichumspecies in NCBI database search. The pathogenicity of Colletotrichum gloeosporioideson peanut seeds and seedlings at 14 days after sowing result was inoculated with pathogenic fungi with 32.3% and control was 83%. Hence, this study was experimented with the object to reveal seed-borne infections on tropical peanut in Malaysia.